ON THE RESPONSE OF IMPACTING COMPLIANT FLEX RUN (Nigerian Journal of Technology, 2017)
Damage caused by impacts of structures can result in catastrophic failure, including huge loss of life. A typical example involves a Flexrun which is particularly vulnerable to several impacts on the ground surface. It is, therefore, becoming increasingly important to be able to model and predict such phenomena. The impact of an impacting compliant system such as a Flexrun on the ground surface is simulated by the general purpose explicit dynamic finite element program LS-DYNA. The complicated geometry has been modeled in Solid Edge ST6 before being imported into LS PrePost/LS-DYNA for the required analysis. The response characteristics of the Flexrun show the effect of impacting velocity on strain and stress histories of the mechanism. Results reveal that within the impacting velocity of 15m/s, the effective stress and strain responses remain unchanged.http://dx.doi.org/10.4314/njt.v36i2.28